Interfacial properties of hot-isostatically-pressed metal-matrix composites - Lee, Li Ling. (2009)
Metal-matrix composites are gaining widespread applications in the industry. However, the development of metal-matrix composites and other composites are hindered by a lack of understanding of the interfacial properties between the matrix and the reinforcement. The fibre-matrix interface of a fibre-reinforced composite plays an important role in determining the bulk mechanical properties, such as strength and toughness, of the composite. The interfacial properties include the interfacial shear strength, interfacial frictional stress and shrinkage pressure.